Banco de sementes e fluxo gênico de azevém sensível e resistente ao herbicida glifosato - Galvan, Jônatas (2013)
The ryegrass is a species of wide use in Rio Grande do Sul. Even though its remarkable beneficial importance, this species has become a weed widely relevant to farming systems in southern Brazil, especially with the occurrence of glyphosate-resistant biotypes. Therefore, it is essential to know the characteristics of this species, in order to subsidize funds for its effective control. Aimed to study the effect of different crop and soil management systems on seedbanks; viability of seeds buried in soil over time; seedling emergence according to the sowing depth, cover crop soil and soil compaction; limiting stage to apply herbicides in order to prevent viable seed production; gene flow of glyphosate resistance between plants from resistant and sensitive genotypes. The experiments were conduct from March 2010 to December 2012. The area used for the study of seedbanks kept fallow, which evaluated the effect of soil scarification, and crop sequences fallow/soybean, wheat/soybean, black oats/soybean and black oats/corn. For seed viability, the seeds were buried, and every three months for two years, exhumed. The emergence was evaluated by exposing the seeds in eight depths, three compression levels and three levels of cover crops. Ryegrass plants were exposed to herbicide in ten stages of development and the seeds from such plants were tested for viability and germination. Gene flow was estimated from the exposure of sensitive ryegrass plants at different distances from glyphosate resistant plants. It was observed that the seedbanks were affected by the crops sequence in the area, and it is possible to reduce it drastically in two years. The seeds viability of in the soil was also reduced, so that at 22 months viability decreased from 92% to approximately 7%. The emergence was affected by sowing depth, where at depths greater than five centimetres emergence percentage is less than 7%. The stage limit to apply herbicides in order to prevent the production of viable seeds was full anthesis. It was not possible to identify gene flow between glyphosate resistant and sensitive ryegrass, possibly due to the asynchrony of flowering among biotypes. It is concluded that if adopted appropriate measures for management, ryegrass may have its buried seeds and its establishment in the area drastically reduced in two years